2004
DOI: 10.1111/j.1440-1754.2004.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

ASCIA guidelines for prevention of food anaphylactic reactions in schools, preschools and child‐care centres

Abstract: These guidelines have been developed by the anaphylaxis working party of the Australasian Society of Clinical Immunology and Allergy to provide advice for minimizing the risk of food-induced anaphylaxis in schools, preschools and child-care centres. The guidelines outline four steps for the prevention of food anaphylactic reactions in children at risk and food policy measures specific to school age and preschool age children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…2 School personnel are required to be familiar with food allergies, and an action plan for allergic emergencies should be developed for every school. 4,5 Adrenaline is regarded as the first-line therapy for anaphylaxis. Nowak-Wegrzyn et al 2 have shown that this drug has been administered to children in almost 15% of accidental cases in schools.…”
Section: Introductionmentioning
confidence: 99%
“…2 School personnel are required to be familiar with food allergies, and an action plan for allergic emergencies should be developed for every school. 4,5 Adrenaline is regarded as the first-line therapy for anaphylaxis. Nowak-Wegrzyn et al 2 have shown that this drug has been administered to children in almost 15% of accidental cases in schools.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an "allergen-aware" table should include the child's friends who are eating safe meals. Experts have not espoused blanket "bans" on foods, 32 particularly because peanut butter, milk, egg, and other common allergens may be a protein staple of another child's diet. In rare instances, individual schools or classrooms might pursue these options.…”
Section: Best-practice Strategiesmentioning
confidence: 99%
“…The management of allergy and anaphylaxis to peanut is outlined in the Australasian Society of Clinical Immunology and Allergy guidelines 5 where parents are encouraged to take their child to a doctor to confirm a diagnosis of peanut allergy and have an anaphylaxis action plan in place.…”
mentioning
confidence: 99%